Learn AppleScript The Comprehensive Guide to Scripting and Automation on Mac OS X - Sanderson, Hamish; Rosenthal, Hanaan; Piper, Ian; Wainwright, Barry; Levy, Emmanuel; Monihart, Harald; Williams, Craig; Stanley, Shane (Apress : Imprint: Apress, 2009)
AppleScript is an English-like, easy-to-understand scripting language built into every Mac. AppleScript can automate hundreds of AppleScript-able applications, performing tasks both large and small, complex and simple. Learn AppleScript: The Comprehensive Guide to Scripting and Automation on Mac OS X, Third Edition has been completely updated for Mac OS X Snow Leopard. It's all here, with an emphasis on practical information that will help you solve any automation problem-from the most mundane repetitive tasks to highly integrated workflows of complex systems. Friendly enough for beginners, detailed enough for advanced AppleScripters Includes major contributions from expert AppleScripters: Emmanuel Levy, Harald Monihart, Ian Piper, Shane Stanley, Barry Wainwright, Craig Williams, and foreword by AppleScript inventor, William Cook.